EU trade in financial services with ASEAN, policy coherence for development and financial crisis - Robles, Alfredo C. (Animo Repository, 2014)
In the wake of the financial crisis, negotiating free trade agreements (FTAs) with Southeast Asia has become a priority for the European Union (EU). Paradoxically, all the indications are that the EU will demand that Indonesia, Malaysia, the Philippines and Thailand liberalize financial services trade with the EU. This article asks whether the EU's policy undermines coherence between EU trade and development policies. It argues that the EU and Association of Southeast Asian Nations (ASEAN) agree that financial services are crucial for development, but that they differ on the approach to liberalization: the EU advocates broad-ranging liberalization, whereas ASEAN countries favour a cautious approach, conditioned by their experience of the Asian financial crisis. In view of this divergence, the EU will have to rethink its approach to financial services trade liberalization in negotiations with ASEAN countries. © 2014 John Wiley & Sons Ltd.